Determinants of uptake of pentavalent vaccine in Benin city, Southern Nigeria - Ogboghodo, Esohe Olivia; Esene, Hendrith A.; Okojie, Obehi H. (International Journal Of Community Medicine And Public Health, 2016)
Background: The Nigerian government in 2012 introduced the pentavalent vaccine into her routine immunization schedule with a view to fast track reduction in child mortality. Despite the advantages of pentavalent vaccine, it has been linked to adverse effects following immunizations including clusters of infant deaths. The objective of the study was to assess knowledge, attitude and experience of care-givers whose under-fives are receiving pentavalent vaccines as determinants of uptake of the vaccine in Benin city. Methods: A descriptive cross-sectional study design was utilized for this study. Data was analyzed using IBM SPSS version 21.0 software. The level of significance was set at p<0.05. A total of 720 care-givers with mean age (SD) of 29.02±4.8 years participated in this study. Results: The About three-quarters 554 (76.9%) of caregivers had a good knowledge on pentavalent vaccines. Good knowledge increased with increasing level of education and being married (p≤0.001 and p=0.015 respectively). Majority, 568 (78.9%), of caregivers had a positive attitude towards the pentavalent vaccination. With increasing level of education, there was an increase in the proportion of caregivers who had a positive attitude towards the vaccine (p≤0.001). Conclusions: Two hundred (27.8%) caregivers had children who had experienced at least a side effect following pentavalent vaccination. Of these, 171 (85.5%) were willing to continue with the vaccine despite AEFIs experienced.